Oxidation effects on the SERS response of silver nanoprism arrays. Issue 1 (23rd December 2016) - Michieli, Niccolò; Pilot, Roberto; Russo, Valentina; Scian, Carlo; Todescato, Francesco; Signorini, Raffaella; Agnoli, Stefano; Cesca, Tiziana; Bozio, Renato; Mattei, Giovanni
Abstract : Oxidation effects on SERS response of Ag nanoprism arrays are interpreted by FEM simulations of the local-field distribution around the nanoprisms. Abstract : Silver nanostructures are widely employed for Surface Enhanced Raman Scattering (SERS) characterizations owing to their excellent properties of field confinement in plasmonic resonances. However, the strong tendency to oxidation at room temperature of these substrates may represent a major limitation to their performances. In the present work, we investigated in detail the effects of oxidation on the SERS response of a peculiar kind of Ag nanostructured substrates, i.e., bi-dimensional ordered arrangements of Ag nanoprisms synthesized by nanosphere lithography. Particularly, wavelength-scanned SERS measurements were performed on Ag nanoprism arrays with a different level of oxidation to determine the SERS enhancement curves as a function of the excitation wavelength around the dipolar plasmonic resonance of the arrays. The experimental results were compared with those obtained by finite elements method simulations. With this approach, we were able to decouple the effects of spectral shift and decrease of the maximum value of the SERS enhancement observed for the different oxidation conditions. The results could be interpreted taking into account the inhomogeneities of the electromagnetic field distribution around the Ag nanostructures, as demonstrated by the simulations.